Delocalization of electron states in n-Si at low temperatures - A. L. Danilyuk; A. G. Trafimenko; A. K. Fedotov; S. L. Prischepa (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
We report on the electric transport properties of Si heavily doped with Sb in the temperature range of 1.9 - 3.0 K and at current density of J < 0.2 A/cm2. Based on the analysis of the current - voltage characteristics, the resistance values at different current densities are obtained. It was found that an increase in current changes the sign of the temperature coefficient of resistance. At J < 0,045 А/cm2, the temperature coefficient of resistance is positive, whereas when the current density exceeds the value of 0,045 А/cm2 it becomes negative. To explain this current crossover in the sign of the temperature coefficient of resistance, we performed Hall measurements at a temperature of 2 K, which allowed us to determine the values of the concentration of charge carriers and their mobility. Based on these measurements and taking into account the concentration instability model, we obtained current dependences of the parameters describing the electric transport in semiconductors, such as activation energy, non-equilibrium concentration of charge carriers, mobility, and scattering time of conduction electrons. As a result of the analysis, it was found that the change in the sign of the temperature coefficient of resistance with an increase in current can be explained by the exchange of electrons between the upper Hubbard band, formed by the capture of injected electrons by neutral impurity atoms, and the edge of the conduction band. In this case, delocalization of electronic states occurs with an increase in current. The data obtained are in good agreement with the proposed hypothesis. Possible delocalization mechanisms are considered by analyzing the electron scattering time. As a result, it was found that electron-electron interactions caused by the Coulomb potential are dominant.